Determinants of Healthcare Services for Aged Women in Rural Bangladesh - Dipika Chandra; Delip Kumar Mondal; Rina Aktar, (Indian Journal of Social Science and Literature (IJSSL), 2024)
In Bangladesh, one of the world’s poorest nations, a significant share of the deprived inhabitants are elderly women who live in rural regions with little access to healthcare. The primary goal of this investigation was to analyse the determinant of healthcare services for aged women in rural Bangladesh. This study was conducted using survey research method through interview schedule. It was carried out in four villages in the Satkhira district. It was followed by purposive sampling and a sample size of 260 was selected. The study revealed that 53.1 percent of the respondent took medical help promptly during the time of illness. Besides this 73.1 percent of the respondent took medical care from a qualified doctor and only 42.2 percent of the respondent get the old allowance. However, nature of the treatment was influenced by the distance to get health facility (p<.001) and response in seeking health care (p<.001). The results indicate that the head of the household’s year of schooling (p=.001) and monthly household income (p. =001) had a significant link with the response to seeking health care.